Polyandry blocks gene drive in a wild house mouse population - Andri Manser (Nature Portfolio, 2020)
This study resolves a long-standing mystery of why t haplotypes, an example of selfish genes, have persisted at unexpectedly low frequencies in wild mouse populations. It shows that multiple mating by females, which is more common at higher mouse population densities, decreases the frequency of driving t haplotypes.